Feminism: Representation of Margaret and Kate in Sydney Sheldon’s Novel Master of the Game - Yohana. RJ. Sihombing; I Wayan Dirgayasa (State University of Medan, 2015)
This study deals with the feminism representation of Margaret and Kate in SydneySheldon’s novel Master of the Game. The objectives are to describe thedifferences and similarities of two woman characterizations namely Margaret andKate and to reveal the feminism value and varieties which are represented by thetwo characters. This study was conducted with the descriptive qualitative method.The source of data was Sydney Sheldon’s novel Master of the Game. The datawere collected by the documentary technique and the instruments weredocumentary sheets. The data which were derived with the feminism analysisshow that each character is differently presented in the novel. The study resultsthat (1) The two characters appear dominantly divergent. Margaret is powerlessand obedient woman whereas Kate is powerful and rebellious woman. (2) Thefeminism values presented in their each work (career), relationship and family.Margaret represents the woman who is not a professional business woman andstays with old fashioned mannered woman, she is a true lover fighting for her loveadmission and she is controlled by her father with patriarchal values supposingher to do chores. Meanwhile Kate is a master of business without manner butbrain, she is a true lover striking to be loved and she is a woman living out ofman’s control and with obsession (3) The varieties of feminism are differentlyshown by the treatments and behaviors of the two characters. Margaretdominantly represents the Liberal feminism in which she fights to be equal withthe man whereas Kate tends to present development feminism as she leads anddoes more than man.